The Cambridge companion to political theology - Hovey, Craig, 1974-; Phillips, Elizabeth, 1973- (Cambridge University, UK., 2015)
"Interest in political theology has surged in recent years, and this accessible volume provides a focused overview of the field. Many are asking serious questions about religious faith in secular societies, the origin and function of democratic polities, worldwide economic challenges, the shift of Christianity's center of gravity to the global south, and anxieties related to bold and even violent assertions of theologically determined political ideas. In fourteen original essays, authors examine Christian political theology in order to clarify the contemporary discourse and some of its most important themes and issues. These include up-to-date, critical engagements with historical figures like Augustine, Thomas Aquinas, and Immanuel Kant; discussions of how the Bible functions theopolitically; and introductions to key movements such as liberation theology, Catholic social teaching, and radical orthodoxy. An invaluable resource for students and scholars in theology, the Companion will also be beneficial to those in history, philosophy, and politics"--
Machine generated contents note: Part I. The Shape of Contemporary Political Theology: 1. European political theology Jurgen Moltmann; 2. Liberation theology Miguel de la Torre; 3. Public theology Hak Joon Lee; 4. Catholic social teaching Lisa Sowle Cahill; 5. Protestant social ethics D. Stephen Long; 6. Postliberalism and radical orthodoxy Daniel M. Bell, Jr; 7. Postcolonial theology Susan Abraham; Part II. Contemporary Questions in Political Theology: 8. Scripture Christopher Rowland; 9. Augustinianisms and Thomisms Eric Gregory and Joseph Clair; 10. Liberalism and democracy Craig Hovey; 11. Capitalism and global economics Philip Goodchild; 12. Political theology as threat William T. Cavanaugh; 13. Good rule Peter J. Leithart; 14. Eschatology and apocalyptic Elizabeth Phillips
Includes bibliographical references and index.
Keywords: Political theology; Christianity and politics